Factors That Influence the Extensional Rheological Property of Saliva - Vijay, Amrita; Inui, Taichi; Dodds, Michael; Proctor, Gordon; Carpenter, Guy (PloS one, 2015)
The spinnbarkeit of saliva reflects the ability of saliva to adhere to surfaces within the mouth, thereby serving as a protective role and aiding in lubrication. Therefore, alterations in the extensional rheology of saliva may result in the loss in adhesiveness or the ability to bind onto surfaces. Mucin glycoproteins and their structures are known to be important factors for the extensional rheological properties of saliva. The conformation of mucin depends on factors such as pH and ionic strength. Chewing is one of the main stimuli for salivary secretion but creates significant sheer stress on the salivary film which could influence mouthfeel perceptions. The current study investigates the possible factors which affect the extensional rheological properties of saliva by comparing submandibular/sublingual saliva with different oral stimuli within the same group of subjects. Unstimulated and stimulated saliva (chew, smell and taste) salivas were collected primarily from submandibular/sublingual glands. The saliva samples were measured for Spinnbarkeit followed by the measuring mucin, total protein, total calcium and bicarbonate concentrations. The results indicated correlations between rheological properties and mucin/ion concentrations. However, chewing stimulated submandibular/sublingual saliva is shown to have significantly lower Spinnbarkeit, but factors such as mucin, protein and calcium concentrations did not account for this variation. Analysis of the concentration of bicarbonate and pH appears to suggest that it has a prominent effect on extensional rheology of saliva.